2023
DOI: 10.1007/s13668-023-00503-x
|View full text |Cite
|
Sign up to set email alerts
|

How Food Choices Impact on Male Fertility

Giulia Pecora,
Francesca Sciarra,
Elena Gangitano
et al.

Abstract: Purpose of Review Increasing evidence on the significance of nutrition in reproduction is emerging from both animal and human studies, suggesting an association between nutrition and male fertility. Here, we have highlighted the impact of the various food groups on reproductive hormones and on spermatogenesis, and the effects of classical and latest dietary patterns such as Mediterranean diet, Western diet, intermittent fasting, ketogenic diet, and vegan/vegetarian diet on male fertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
1
2
0
Order By: Relevance
“…Likewise, the vegans displayed the most fundamentally healthy dietary behavior considering the consumption of whole plant foods, including legumes, nuts, and pulses, and fruit and vegetables, with significant differences across the subgroups (p < 0.05). This finding is consistent with the level of plant protein intake reported by the vegan subgroup, which has been shown to significantly reduce the risk of cardiovascular disease, all-cause mortality, and even male infertility when substituting for many varieties of animal protein sources [36,69,70]. Interestingly, it was found that the vegans (e.g., the people consuming only plant-based foods) had the highest protein intake overall, with a significant difference across the diet types.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Likewise, the vegans displayed the most fundamentally healthy dietary behavior considering the consumption of whole plant foods, including legumes, nuts, and pulses, and fruit and vegetables, with significant differences across the subgroups (p < 0.05). This finding is consistent with the level of plant protein intake reported by the vegan subgroup, which has been shown to significantly reduce the risk of cardiovascular disease, all-cause mortality, and even male infertility when substituting for many varieties of animal protein sources [36,69,70]. Interestingly, it was found that the vegans (e.g., the people consuming only plant-based foods) had the highest protein intake overall, with a significant difference across the diet types.…”
Section: Discussionsupporting
confidence: 89%
“…According to the com-b model, however, a person’s capabilities and opportunities may also, in turn, reflect dietary behavior [ 92 ]. Given the strong societal foundation that is visible around the world concerning the belief that meat consumption is necessary for reproductivity and survival, strength, or even evolution [ 30 , 36 , 37 , 71 , 82 ], when a person refuses to consume meat, interpersonal disputes typically arise due to the phenomenon of cognitive dissonance (e.g., when two or more personal values conflict) [ 93 ]. Such interpersonal communication arising from the personal choice not to eat has been so powerful it has effectively been used to stop mass violence, for example [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation